THE SECTION OF CULTIVATED PLANTS IN THE CENTENNIAL HISTORY OF THE RUSSIAN BOTANICAL SOCIETY (RBS) - T. N. Smekalova (Труды по прикладной ботанике, генетике и селекции, 2018)
The article presents a brief history of the Russian Botanical Society (RBS) and its Section of Cultivated Plants.